If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 = -8 + 3a + 4 Reorder the terms: -4 = -8 + 4 + 3a Combine like terms: -8 + 4 = -4 -4 = -4 + 3a Add '4' to each side of the equation. -4 + 4 = -4 + 4 + 3a Combine like terms: -4 + 4 = 0 0 = -4 + 4 + 3a Combine like terms: -4 + 4 = 0 0 = 0 + 3a 0 = 3a Solving 0 = 3a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3a' to each side of the equation. 0 + -3a = 3a + -3a Remove the zero: -3a = 3a + -3a Combine like terms: 3a + -3a = 0 -3a = 0 Divide each side by '-3'. a = 0 Simplifying a = 0
| 10+9d=210 | | 9y+y+5=45 | | 18+15x-25x^2=0 | | x^2=130 | | -(8-2x)=3(3x-6)-7x-10 | | 20=2a+8a | | 1760+20x=1760 | | 720=470+2x | | -6a-5a+b-1= | | (x^2)+x=8 | | 11(g+5)=2(g+9) | | 10=4-(x-2) | | 300-7[4(3+5)]+27=a | | 2+(-3)+6= | | -2/5x+21/5=1/4x-11/2 | | 0.33x=-5 | | [216-9/23]4 | | Z-12=30 | | 1.5(3b-7)+15b=90 | | Cos^2x-2=0 | | 3w+7=9 | | 51=-5x-3(x+15) | | 0=-2(x-3)+2x+2 | | -3(6r+2)+6r=-30-6r | | v=3.14/3^2h | | 5h+2(11h)=-5 | | 6x-1=4x+10 | | 2(2-7y)+3=-2y+6-12y | | 12yx^4/10yx^8 | | 10-2y=3y | | -32=-(-5x)+x-2 | | x^2+2x-12=3x^2+8x-5 |